Tracing English Elements in Finnish Literature Translation : Understanding Variation Between The Hunger Games –translations Through the Lens of Interference - Puro, Nea (My University, 2026)
This thesis examines the variation of foreign language matter in two translations of Suzanne Collins’ The Hunger Games book series using Gideon Toury’s law of interference (1995) as a theoretical framework. The main data is the Finnish translation of Sunrise on the Reaping (2025), with a comparative basis being the translation of The Hunger Games (2008). The interference is identified by examining the translation techniques utilized by translators Helene Bützow and Einari Aaltonen and relating the data to socio-cultural aspects and the context of the book. The aim of this thesis is to evaluate how English language elements manifest themselves in Finnish literature translation, and how the variation of those elements can affect the coherence of the book series. This was done through reading both the English and Finnish versions of the book and choosing ten examples from the Finnish translation that showed atypical linguistic traits to the Finnish language. The analysis shows that while English elements have increased within the book series, sometimes resulting in inconsistencies between the connected storylines of the books, negative transfer does not necessarily occur in all cases. This study is a case study, meaning that the results are only applicable to the Hunger Games series, and can not be generalized.
Keywords: Interference, The Hunger Games, Literature Translation, Language Transfer